What drives publishing in top management journals: an analysis of language, quantitative competency and financial support. (2017) - Falaster, Christian; Ferreira, Manuel Portugal
Publishing in top-level academic journals is both a personal achievement and a crucial requirement in every scholar's career, albeit the institutional demands vary markedly among countries and institutions. In this study, we scrutinise how the effect of a set of factors - expenditure on education, R'D, English language proficiency and math competency - may influence the likelihood of publishing in top-ranked management journals. We have analysed the entire records of published articles in four top management journals over the past six years (2009-2014). On a sample of 1, 322 articles, the results revealed that top level publishing is positively influenced by the national expenditure on R&D and English proficiency. The quantitative competency proved to have no effect on the ability to publish in top management journals, which is surprising given the current emphasis on quantitative studies. The results are discussed to provide scholars some guidelines to improve their publications in top journals.